Analysis of wind-induced responses of landing assembled Chinese solar greenhouses. (August 2022) - Wang, Cong; Jiang, Yingchun; Wang, Tieliang; Xu, Zhanyang; Bai, Yikui
Abstract : The wind-induced responses of a landing assembled Chinese solar greenhouse (CSG) were investigated by considering fluctuating wind speeds. Fluctuating wind speeds were simulated using the harmony superposition method. The dynamic properties of the CSG were extracted using modal analysis. The displacement and bending stress of the CSG under mean and instantaneous wind loads were compared. The results showed that both the displacement and bending stress under the south wind (0° direction) were lower than those under the north wind (180° direction). When the wind direction was 0°, the maximum displacement and bending stress under instantaneous wind loads were 1.926 and 1.673 times those under mean wind loads, respectively. When the wind direction was 180°, the maximum displacement and bending stress under instantaneous wind loads were 2.054 and 2.003 times those under mean wind loads, respectively. To estimate the nodal displacement wind vibration coefficients and quantify the amplification effects of instantaneous wind loads, the effects of the structural damping ratios, sectional dimensions, and simulated wind speed samples on the wind-induced responses of the CSG were investigated. Finally, a global nodal displacement wind vibration coefficient of 2.0 is recommended for the case study. These results can provide a reference for the wind-resistance design of landing assembled CSG. Highlights: Fluctuating wind speeds were simulated using the harmony superposition method. The wind-induced responses of a landing assembled CSG were investigated. The dynamic properties of the CSG were extracted using modal analysis. The nodal displacement wind vibration coefficients were obtained.